The Effect of Rice and Green Banana Flours Replacement to Wheat Flour in Pumpkin Muffin on Physical Properties, Nutritional Composition and Sensory Acceptance - Norlelawati Arifin; Nurnasuha Siran; Rafiu Agbaje (Akademia Baru Publishing, 2026)
Non-Indexed Publication